2021
DOI: 10.1039/d1fo02447g
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular docking of peptides from Mizuhopecten yessoensis myosin as human bitter taste receptor T2R14 blockers

Abstract: Bitter taste receptor 14(T2R14) is one of the most widely regulated bitter taste Receptors(T2Rs), and plays a vital role in the research of T2Rs blockers. In this study, potential T2R14...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In a study by Lin et al, 18 it was found that N-acetyl-valine/Leu/Ile/Met/Phe were kokumi complexes that could enhance sweetness, umami, and saltiness. Zhao et al 28 identified potential bitter taste receptor T2R14 blockers from the myosin of Mizuhopecten yessoensis and verified the in vitro T2R14 blocking activity of the selected peptides by electronic tongue. The results showed that QRPR had T2R14 blocking activity with an IC 50 value of 256.69 ± 1.91 μM.…”
Section: Nmr Characterization Of Lpmentioning
confidence: 98%
“…In a study by Lin et al, 18 it was found that N-acetyl-valine/Leu/Ile/Met/Phe were kokumi complexes that could enhance sweetness, umami, and saltiness. Zhao et al 28 identified potential bitter taste receptor T2R14 blockers from the myosin of Mizuhopecten yessoensis and verified the in vitro T2R14 blocking activity of the selected peptides by electronic tongue. The results showed that QRPR had T2R14 blocking activity with an IC 50 value of 256.69 ± 1.91 μM.…”
Section: Nmr Characterization Of Lpmentioning
confidence: 98%
“…However, given that viruses do not themselves produce the same repertoire of metabolites compared with bacteria and fungi, it is harder to speculate how viruses could activate taste receptors. However, because peptides can be T2R agonists [ 30 , 297 ] or blockers [ 286 , 298 , 299 ], it is in theory possible that viral proteins can activate one or more taste receptors. It may also be that taste receptors detect metabolites released by cells during viral replication or budding or during viral-induced apoptosis.…”
Section: Conclusion and Remaining Questionsmentioning
confidence: 99%
“…Among which, 8 peptides (SC, DM, SM, CR, DSW, CQR, CGSR, and KPTW) were non-toxic in the toxicity prediction. The '-CDOCKER_ENERGY' values reflected the bingding affinity between the T2R14 receptor and the peptides [9] . Eight peptides (SC, DM, SM, CR, DSW, CQR, CGSR, and KPTW) were used for the molecular docking, and their '-CDOCKER_ENERGY' values were 152.…”
Section: Virtual Screening Of Potential Bitter Receptor T2r14 Blockin...mentioning
confidence: 99%
“…However, only a few blockers have been identified that can against specific T2Rs on a receptor level [3] . Currently, bioactive peptides have attracted much attention and are widely applied in the food industry, chemistry and biology with the advantages of safety, slight side-effects, diverse functions and selectivity [9] . The peptide QRPR from myosin of Mizuhopecten yessoensis was demonstrated as the potential candidate for suppressing bitterness [10] .…”
Section: Introductionmentioning
confidence: 99%